2017
DOI: 10.1038/s41598-017-02783-0
|View full text |Cite
|
Sign up to set email alerts
|

Tetraploid embryonic stem cells can contribute to the development of chimeric fetuses and chimeric extraembryonic tissues

Abstract: Our study examined the in vivo chimeric and survival capacities of chimeras created by injecting tetraploid embryonic stem cells (ESCs) expressing green fluorescent protein (GFP) into diploid embryos. At 3.5 days post-coitum (dpc) and 4.5 dpc, the tetraploid ESCs were able to contribute to the inner cell mass (ICM) just as diploid ESCs tagged with GFP. At 6.5 dpc, 8.0 dpc and 10.5 dpc, the tetraploid ESCs manifested in the same location as the diploid ESCs. The GFP cells in the extraembryonic tissues and fetus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…1B right column arrowheads). Previous studies reported that horizontal morphology of colonies was similar between diploid and tetraploid ESCs as assessed using inverted microscopes [ 2 , 4 , 11 ], and this vertical analysis strongly supported the similarity. Here, we showed the histological utility of the new method of vertically sectioning stereoscopic cell colonies, such as mouse embryonic stem cells, for the first time.…”
supporting
confidence: 77%
“…1B right column arrowheads). Previous studies reported that horizontal morphology of colonies was similar between diploid and tetraploid ESCs as assessed using inverted microscopes [ 2 , 4 , 11 ], and this vertical analysis strongly supported the similarity. Here, we showed the histological utility of the new method of vertically sectioning stereoscopic cell colonies, such as mouse embryonic stem cells, for the first time.…”
supporting
confidence: 77%
“…chromosomal instability in preimplantation cells (Paim and FitzHarris, 2019) chimeric mouse embryos with a mixture of diploid and tetraploid cells will develop through preimplantation before dying during peri-implantation (Horii et al, 2015). Notably, tetraploid sensitivity in vivo appears to be specific to the epiblast as embryos with tetraploid trophoblast cells and diploid epiblast cells can generate live pups (Wen et al, 2017). Mouse embryos containing a mixture of diploid and aneuploid cells will also develop to peri-implantation before the aneuploid cells are specifically depleted in the epiblast through apoptosis (Bolton et al, 2016).…”
Section: Rapid Proliferationmentioning
confidence: 99%
“…Other reports have shown that the more polyploidization, the less the number of the inner cell mass in blastocysts (Liu et al, 2004;Lei et al, 2009). Tetraploid embryonic stem cells established from mouse tetraploid blastocysts have shown increment in apoptosis, and decrement of proliferation rate and meiosis-related gene expression (Horii et al, 2015;Imai et al, 2015;Wen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%